Aging-Related Endothelial Progenitor Cell Dysfunction and Its Association with IL-17 and IL-23 in HFmrEF Patients. (26th June 2022) - Zeng, Lijin; Zhang, Cong; Cai, Guoyi; Zhang, Bin; Huang, Zixia; Wu, Mingyue; Zhu, Yuanting; Luo, Liang; He, Hao; Yang, Zhen
Abstract : Background . Aging is an independent risk factor for heart failure (HF), and endothelial progenitor cell (EPC) function decreases with aging. Here, we further investigated whether age has a detrimental effect on circulating EPC function in HF with mildly reduced ejection fraction (HFmrEF) and its relationship with systemic inflammation. Methods . 58 HFmrEF patients were recruited. The adhesive, migrative, and proliferative activities of circulating EPCs, MAGGIC scores, and plasma interleukin (IL)-17 and IL-23 levels of these patients were assessed. Results . Older patients with HFmrEF had higher MAGGIC scores and lower circulating EPC adhesion, migration, and proliferation than younger patients. The similar tendency was observed in plasma IL-17 and IL-23 levels. The EPC functions were negatively associated with MAGGIC scores and plasma IL-17 or IL-23 levels. Conclusions . In patients with HFmrEF, aging leads to attenuated circulating EPC function, which is correlated with disease severity and systemic inflammation. The present investigation provides some novel insights into the mechanism and intervention targets of HFmrEF.